ChemInform Abstract: Polyoxomolybdate‐Stabilized Cu2O Nanoparticles as an Efficient Catalyst for the Azide—Alkyne Cycloaddition. Issue 41 (September 2016) - Amini, Mojtaba; Naslhajian, Hadi; F. Farnia, S. Morteza; Kyoung Kang, Hee; Gautam, Sanjeev; Chae, Keun Hwa
Abstract: For the first time, polyoxomolybdate‐stabilized Cu2 O nanoparticles are utilized as a recyclable catalyst for the Huisgen 1, 3‐dipolar cycloaddition reaction of terminal alkynes, aryl/alkyl halides and Na3 to afford 1, 2, 3‐triazole derivatives (III) in good to excellent yields.